1994
DOI: 10.1002/ajmg.1320520204
|View full text |Cite
|
Sign up to set email alerts
|

Mental retardation and Ullrich‐Turner syndrome in cases with 45,X/46,X,+ mar: Additional support for the loss of the X‐inactivation center hypothesis

Abstract: Four cases having mosaicism for a small marker or ring [45,X/46,X,+mar or 45,X/46,X,+r] chromosome were ascertained following cytogenetic studies requested because of minor anomalies (cases 1, 3, and 4) and/or short stature (cases 2 and 4). While all 4 cases had traits typical of Ullrich-Turner syndrome (UTS), cases 1, 3, and 4 had manifestations not usually present in UTS, including unusual facial appearance, mental retardation/developmental delay (MR/DD) (cases 3 and 4), and syndactylies (case 1). The facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Unusual facial appearance, MR/DD, and syndactylies were observed. They noted that among their patients, mental retardation was noted most frequently in the cases having at least 50% mosaicism for the marker [Cole et al 1994]. Similar features were found in our patient, namely a Turner syndrome picture with abnormal facial appearance, MR, short stature, and DD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unusual facial appearance, MR/DD, and syndactylies were observed. They noted that among their patients, mental retardation was noted most frequently in the cases having at least 50% mosaicism for the marker [Cole et al 1994]. Similar features were found in our patient, namely a Turner syndrome picture with abnormal facial appearance, MR, short stature, and DD.…”
Section: Discussionsupporting
confidence: 86%
“…This concurs with the observations of the patient presented here with the absence of ovaries detected by the USG examination. Cole et al [1994] and Liehr et al [2007] reported MR for these Turner syndrome variant patients. Badeschi and colleagues [2008] described a male with severe MR with duplication on the X chromosome Xq12 to Xq12.1, which contains the OPHN1 gene.…”
Section: Discussionmentioning
confidence: 94%
“…Anomalous X inactivation has been postulated to be associated with NTDs [James, 1988], especially in cases of monozygotic twins. Faulty X inactivation, as shown in cases of small marker chromosomes that do not express XIST, may result in mental retardation and malformation [Cohen et al, 1967;Van Dyke et al, 1992;Cole et al, 1994;Kushnick et al, 1987;Migeon et al, 1993Migeon et al, , 1994Wolff et al, 1994]. Our observation of a small r(X) occurring in a female fetus with a NTD commonly showing female excess suggests that faulty X inactivation may result in abnormalities of neurulation.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to mental retardation [Kushnick et al, 1987;Van Dyke et al, 1992;Cole et al, 1994;Callen et al, 1995;Cantú et al, 1995], some of these patients have limb defects [Kushnick et al, 1987;Wolff et al, 1994;Collins et al, 1994;Cantú et al, 1995], agenesis of corpus callosum [El Abd et al, 1997], Kabuki makeup facial changes [Dennis et al, 1993;McGinniss et al, 1997;El Abd et al, 1997], and prune belly sequence [Guillén et al, 1997]. More severe phenotypes, especially mental retardation, have been shown to be associated with a lack of inactivation of the small ring X chromosome due to deletion of the X inactivation center (XIC) or lack of expression of the XIST gene (X inactivation specific transcript) [Van Dyke et al, 1992;Zenger-Hain et al, 1993;Migeon et al, 1994;Callen et al, 1995].…”
mentioning
confidence: 99%
“…Although the large r(X) occurrences have already been described in Turner mosaic, in females with moderate clinical manifestations and, even more, able to undergo spontaneous pregnancies [3][4][5], the tiny ones are frequently associated with a more severe phenotype and/or with mental retardation [6][7][8][9]. This phenomenon has been attributed to the inability of these small abnormal X chromosomes to inactivate, resulting in two active copies of genes in the pericentromeric region [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%